Citizen Resistance and Everyday Security: Rethinking Substantive Democracy under Military Regimes in West Africa - (:unkn) unknown (My University, 2025)
The presentation entitled "Citizen Resistance and Everyday Security: Rethinking Substantive Democracy under Military Regimes in West Africa" analyzes the subtle yet effective strategies developed by populations resisting emerging authoritarian regimes following repeated military coups, notably in Mali since 2020. It highlights how severe restrictions on fundamental freedoms, arbitrary arrests, and censorship have fostered new forms of citizen resilience rooted in daily practices. The talk thus offers an in-depth reflection on the concept of "substantive" democracy, going beyond formal institutional frameworks to concretely address popular aspirations and real security challenges. It advocates a pragmatic redefinition of democracy, adapted to the fragile political contexts currently facing West Africa.
Keywords: African Research